Microwave Photonic Harmonic Down-Conversion Based on Cascaded Four-Wave Mixing in a Semiconductor Optical Amplifier - Xinhai Zou; Shangjian Zhang; Heng Wang; Zhiyao Zhang; Jinjin Li; Yali Zhang; Shuang Liu; Yong Liu (IEEE Photonics Journal, 2018)
A reconfigurable and wideband photonic method is proposed for microwave photonic harmonic down-conversion based on cascaded four-wave mixing in a semiconductor optical amplifier (SOA). The cascaded four-wave mixing in SOA triggers high-order harmonics generation of local oscillator (LO) in the optical domain, and enables microwave down-conversion in the electrical domain with a low-frequency electrical LO. Compared with the conventional photonic method, ours allows microwave down-conversion operation for wide frequency range RF signal with a low-frequency electrical LO, and at the same time it avoids the requirement of complex phase control and heavy driving for the electrical LO. Moreover, it enables reconfigurable down-conversion with frequency tunability. In the demonstration, the 3∼40 GHz RF signals are experimentally down-converted to IF signals below 2 GHz with a low-frequency electrical LO within the range of 5 GHz.